2009
DOI: 10.1007/s11010-009-0277-0
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of an anomalous endocytic compartment in fibroblasts from Sandhoff disease patients

Abstract: Sandhoff disease (SD) is a lysosomal storage disorder due to mutations in the gene encoding for the beta-subunit of beta-hexosaminidase, that result in beta-hexosaminidase A (alphabeta) and beta-hexosaminidase B (betabeta) deficiency. This leads to the storage of GM2 ganglioside in endosomes and lysosomes, which ends in a progressive neurodegeneration. Currently, very little is known about the biochemical pathways leading from GM2 ganglioside accumulation to pathogenesis. Defects in transport and sorting by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Even when a primary defi ciency in a lysosomal glycohydrolase, activator protein, or saposin directly involved in the degradation of GM2 or GM3 ( 52 ) is not present, the accumulation of GM2/GM3 appears to occur, at least in part, in the endosomal/lysosomal system ( 26,29,30,34,53 ) and/or in lipid rafts ( 24,27,33 ). As well as for defi ciencies in catabolic proteins not directly involved in degradation of these gangliosides, defects in traffi cking of gangliosides from endosomes to the Golgi apparatus ( 53,54 ) or from late endosomes to lysosomes ( 55,56 ) also observed in some lysosomal storage diseases can produce similar accumulation. In chronic diseases, such ganglioside accumulation is typically detected in neurons ( 29,30,34,57 ) and, in some cases, in activated microglia ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even when a primary defi ciency in a lysosomal glycohydrolase, activator protein, or saposin directly involved in the degradation of GM2 or GM3 ( 52 ) is not present, the accumulation of GM2/GM3 appears to occur, at least in part, in the endosomal/lysosomal system ( 26,29,30,34,53 ) and/or in lipid rafts ( 24,27,33 ). As well as for defi ciencies in catabolic proteins not directly involved in degradation of these gangliosides, defects in traffi cking of gangliosides from endosomes to the Golgi apparatus ( 53,54 ) or from late endosomes to lysosomes ( 55,56 ) also observed in some lysosomal storage diseases can produce similar accumulation. In chronic diseases, such ganglioside accumulation is typically detected in neurons ( 29,30,34,57 ) and, in some cases, in activated microglia ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…In lysosomal storage diseases such as Sandhoff disease and Niemann‐Pick disease, it has been indicated that accumulated GM2 in neurons are localized mainly in lysosomes/late endosomes because of defective lysosomal degradation and/or defective trafficking of gangliosides from endosomes to the Golgi apparatus (Marks and Pagano 2002; Vitner et al. 2010) or from late endosomes to lysosomes (Tancini et al. 2009; Lloyd‐Evans and Platt 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In lysosomal storage diseases such as Sandhoff disease and Niemann-Pick disease, it has been indicated that accumulated GM2 in neurons are localized mainly in lysosomes/late endosomes because of defective lysosomal degradation and/ or defective trafficking of gangliosides from endosomes to the Golgi apparatus (Marks and Pagano 2002;Vitner et al 2010) or from late endosomes to lysosomes (Tancini et al 2009;Lloyd-Evans and Platt 2010). Ethanol has been shown to induce perturbation in endocytic processes of sphingolipids (Ravasi et al 2002;TomĂĄs et al 2004), which may be related to the observed GM2 accumulation in a late endosome/lysosome/phagolysosome fraction of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that the activation of TFEB, a transcription factor that controls lysosomal biogenesis and function, is accompanied by an increase of mature β-hexosaminidase on cell surface [21]. From a pathological point of view, mutations in the Îą- and β-subunit coding genes lead to the development of Tay-Sachs and Sandhoff diseases, respectively, which are severe lysosomal storage disorders associated with neurodegeneration [22]. In addition, β-hexosaminidase altered expression has been often associated with cancer [23], [24] and namely the presence of Hex S has been observed in leukaemic cells but not in their normal counterparts [25].…”
Section: Introductionmentioning
confidence: 99%